Pengembangan Kurikulum Pesantren As-Sunniyyah Kencong Jember - Mohammad Dasuki (STAIFAS-Press, 2019)
Islamic school as an institution that represents Islamic education in Indonesia has plurality values ​​that should be appreciated. Perspectives on islamic school which are synonymous with conservative ideology and tend to be considered rigid in the face of educational dynamics and the view that pesantren are an ancient institution and only think about the afterlife problems seem to be incorrectly addressed to this islamic school, islamic school As-Sunniyyah Islamic boarding school which is the object of research in this paper is portrait of a islamic school that has successfully organized independent education, including in developing curriculum and learning patterns. The integration between religious and general sciences is the key, in addition to extra activities that encourage students to have multiple talents. The purpose of this study include: 1) obtain information on what causes the development of curriculum in As Sunniyyah Islamic boarding school. 2) reveal the pattern of curriculum development in the As Sunniyyah islamic school.